The Effect of Financial Fundamental Factors on Systemic Risk in LQ45 Companies Listed in Indonesia Stock Exchange - Suryanto Suryanto; Ahmad Johan; Riza Bahtiar Sulistyan (Program Studi Administrasi Bisnis, 2022)
This study aims to analyze the influence of fundamental factors on systematic risk. Fundamental factors are represented by the current ratio (CR), debt to equity ratio (DER), return on equity (ROE), and price earning ratio (PER). While the systematic risk for this study is calculated using the beta value of the stock. The research uses a quantitative approach with verification research methods. The sample used in this study is issuers who are members of the LQ 45 group during the 2017-2021 period. The analysis technique used is multiple regression. The results showed that DER and PER partially affect systematic risk, while CR and ROE partially have no effect on systematic risk. However, simultaneously these factors affect the systematic risk.